PENGARUH TEKNIK RELAKSASI TARIK NAFAS DALAM TERHADAP KECEMASAN IBU HAMIL TRIMESTER III TAHUN 2021 - Karmelia, Mela (Journal of Midwifery Tiara Bunda, 2024)
Background: research on the effect of deep breath relaxation techniques on anxiety of third trimester pregnant women. Relaxation techniques in this study are deep breath relaxation therapy techniques and can reduce anxiety and overcome anxiety in the face of childbirth Research Objectives: To determine the effect of deep breath relaxation techniques on anxiety of third trimester pregnant women. Research Design: this research is experimental research, using quasi experimental (pseudo experiment). The research approach is one group pre test and post test design without using a comparison group (control).The population in this study is all third trimester pregnant women with anxiety.in Sukaluyu Village, Tamansari District as many as 10 third trimester pregnant women. Research Results: Shows that anxiety before and after being given a deep breath technique in getting anxiety p-value 0.005 (p-value <0.05). This shows that the null hypothesis is rejected. So the conclusion that can be drawn is that the deep breath technique affects anxiety in third trimester pregnancy in the city of Bogor, West Java province in 2024.Research Conclusion: to apply the deep breath relaxation technique for handling anxiety in third trimester pregnant women.